Inorganic chemistry - Purcell, Keith F.; Kotz, John C. (New Delhi: Cengage Learning, 1977)
An rare and excellent book for inorganic chemistry, is a little old, but most of the concepts are still the same. Worthy to buy. The book bring chapters as 1) Useful Atomic Concepts 2) Basic concepts of molecular topologies 3) The directed atomic orbital view of chemical bonds 4) The undirected orbital view of chemical bonds 5) The donor/acceptor concept 6) Energetics and structures as guides to main group chemistry 7) Reaction Pathways 8) Synthesis of important classes of non-metal compounds 9) Fundamental concepts for transition metal complexes 10) Coordination chemistry: structural aspects 11) Coordination chemistry: isomerism 12) Coordination chemistry: reaction mechanisms and method of synthesis; electron transfer reactions. 13) Coordination chemistry: reaction mechanisms and method of synthesis; substitution reaction 14) Coordination chemistry: reaction mechanisms and method of synthesis; molecular rearrangements and reactions of coordinated ligands 15) From classical to organometallic transition metal complexes and sixteen and eighteen electron rule 16) Organometallic chemistry: synthesis, structure, and bonding 17) Organometallic compounds: reaction pathways 18) Molecular polyhedral: boron hydrides and metal clusters 19) Biochemical applications. A really complete book and all of this in 197
Compound Index 1097-1104p.; Subject Index 1105-1116p.; Reprint 2012.
Keywords: Coordination chemistry; Organomettallic chemistry; Reaction pathways; Biochemical applications